2017
DOI: 10.1111/ijac.12839
|View full text |Cite
|
Sign up to set email alerts
|

Using calcium sulfate cement—Hydroxypropyl methyl cellulose/sodium alginate composites as substitutes of bone wax

Abstract: Development of alternatives of bone wax to stop blood transfusion occurred in cancellous bone injury is highly deserved clinically. An ideal candidate is supposed to be not only biodegradable, biocompatible, malleable, and cost-effective, but also have comparable mechanical strength to cancellous bone. In the present work, calcium sulfate cement (CSC) based composites modified with hydroxypropyl methyl cellulose (HPMC) or sodium alginate (SA) were prepared. In brief, CSC was combined with 2, 4, 6 wt.% of HPMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…[5] However, bone wax has been associated with inflammation, granuloma formation, hindered osteogenesis and even bone wax migration. [6,7] Possible substitutes of bone wax have been constructed from petroleum-based polymers and inorganic materials, [8,9] which still possess some inherent shortcomings including slow or incomplete degradation and poor effects on anti-inflammation/wound healing. Moreover, biomass-based materials had been particularly appealing for an economical and sustainable society of mankind.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] However, bone wax has been associated with inflammation, granuloma formation, hindered osteogenesis and even bone wax migration. [6,7] Possible substitutes of bone wax have been constructed from petroleum-based polymers and inorganic materials, [8,9] which still possess some inherent shortcomings including slow or incomplete degradation and poor effects on anti-inflammation/wound healing. Moreover, biomass-based materials had been particularly appealing for an economical and sustainable society of mankind.…”
Section: Introductionmentioning
confidence: 99%
“…[24,25] Due to the abundant blood vessels and systolic blood pressure in cancellous bones, bone-defect-induced bleeding is clinically recognized as intractable bleeding due to its sustained bleeding behavior before long-term bone repair. [8,26] Herein, biomass-derived multilayer-structured hemostatic microparticles (MQ x T y ) composed of starches and plant polyphenols were flexibly constructed by layer-by-layer assembly based on negatively charged microporous starch particle (M) cores and multiple quaternized starch (Q + )/T − layers (Figure 1a). Such absorbable microparticles were proposed as advanced biomedical materials to integrate the advantages of M, Q + , and T − and achieve effective treatments of bone defects with intractable bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…The possible mechanism of HPMC action can be summarized into two aspects. On the one hand, it has been shown that HPMC can provide 3D networking for materials such as mixing with collagen [23,40], and without HPMC the material structure was looser so it falls apart easily. It is possible that HPMC provided stronger structure for premixed putty, thus we observed that the anti-washout property was better when there was more HPMC added into the premixed putty (Figure 2A).…”
Section: Discussionmentioning
confidence: 99%
“…The released calcium ions from the material can activate the coagulation cascade when it comes in contact with the blood. The presence of sodium alginate was found to enhance the hemostatic activity with better strength and stability when compared to HPMC by in vitro studies 75 . However, they did not report in vivo studies or address the concerns regarding infection.…”
Section: Progress In Enhancing Sternal Healing Controlling Bleedingmentioning
confidence: 99%
“…However, an in vivo study is necessary to conclude the effects 74 . Zhou et al, 75 developed a material composed of calcium sulfate with hydroxypropyl methyl cellulose (HPMC) or sodium alginate. The fast setting properties of calcium sulfate cement can limit its use and a modifier like HPMC or sodium alginate is necessary to be incorporated to impart cohesiveness.…”
Section: Progress In Enhancing Sternal Healing Controlling Bleedingmentioning
confidence: 99%